Dietary Trans Fatty Acids: Impact on Serum Lipoproteins and Coronary Heart Disease - Ahsan, Raghib (TAJ: Journal of Teachers Association, 2009)
Recently, there has been considerable concern on the atherogenic potential of Trans Fatty Acids (TFA) present in the food products produced with hydrogenated vegetable and marine oils. Health authorities and Food regulatory agencies across the world, including WHO and FAO, have suggested food manufacturers to lower TFA content in their food products and called for a mandatory food labeling on packs for consumer information and protection. doi: 10.3329/taj.v18i2.3198 TAJ 2005; 18(2): 144-148